Entre o twitter e o diário oficial: o princípio da publicidade e os limites entre o público e o privado - Limeira, Lucas dos Santos (Universidade Federal Rural do Semi-Árido, 2019)
This article deals with the action of political actors, especially the members of elective mandates, in the context of the digital platform called Twitter. In this sense, the action of these agents is analyzed under the perspective of the principle of publicity and the fundamental guarantee of access to information, both established in the Federal Constitution of 1988 and enforced in specific legislation. Also, this article demonstrates how Twitter is being used as a political tool and as a true vehicle of publication of acts of interest, relevance and public character, reason for which we must ensure access to such acts to the population, without any restriction. In addition, it’s possible to verify, based on an important American precedent and also in specific movements of some segments Brazilians, that we cannot equate such political actors to simple individuals, even when while using social media and especially when such platforms are used as a public forum and as an extension of their own position they occupy. In this way, it can be concluded that such agents, while members of the Public Administration, shall guide their conduct and their speech based on the guiding principles stamped on article 37, caput, of the Federal Constitution, among which the publicity, making it unthinkable, therefore, the use of blocking tools to users by simple differences, considering that such conduct goes against the constitutionally guaranteed right to access information.
Artigo acadêmico
Keywords: Agentes Políticos; Princípio da Publicidade; Twitter; Political Actors; Principle of Publicity; Twitter; CIENCIAS SOCIAIS APLICADAS::DIREITO